The shorter the better? A follow-up analysis of 10-session psychiatric treatment including the motive-oriented therapeutic relationship for borderline personality disorder. (4th May 2017) - Kramer, Ueli; Stulz, Niklaus; Berthoud, Laurent; Caspar, Franz; Marquet, Pierre; Kolly, Stéphane; De Roten, Yves; Despland, Jean-Nicolas
Abstract: Objective: There is little research on short-term treatments for borderline personality disorder (BPD). While the core changes may occur only in long-term treatments, short-term treatments may enable the study of early generic processes of engagement in therapy and thus inform about effective treatment components. It was shown that a 10-session version of a psychiatric treatment was effective in reducing borderline symptoms at the end of this treatment [Kramer, U., Kolly, S., Berthoud, L., Keller, S., Preisig, M., Caspar, F., … Despland, J.-N. (2014). Effects of motive-oriented therapeutic relationship in a ten-session general psychiatric treatment for borderline personality disorder: A randomized controlled trial. Psychotherapy and Psychosomatics, 83, 176–186.]. Also, it was demonstrated in a randomized design that adding the motive-oriented therapeutic relationship (MOTR), following an individualized case formulation based on Plan Analysis, further increased general outcome after session 10 and had a positive effect on the early changes in self-esteem and alliance.Method: The present study focuses on the follow-up period after this initial treatment, examining treatment density and outcomes after 6 months and service utilization after 12 months. Outcome was measured using the OQ-45.Results: Results on a sub-sample of N = 40 patients with available OQ-45 data at follow-up ( n = 21 for MOTR-treatment, n = 19 for comparison treatment) showed maintenance of gains over the follow-up period, which did not differ between both conditions. It appeared for this sample that MOTR treatments, while using the same number of sessions, lasted more weeks (i.e., lower treatment density, defined as the number of sessions per week), when compared to the treatments without MOTR. Density marginally predicted symptom reduction at follow-up. Patients in MOTR treatments had a greater likelihood of entering structured psychotherapy after the initial sessions than patients in the comparison group.Conclusions: These results are overall consistent with earlier studies on short-term treatments for BPD and underline the importance of individualizing interventions, by using case formulations that rely on idiographic methods and integrative concepts.